A 60 μm-Long Fiber-to-Chip Edge Coupler Assisted by Subwavelength Grating Structure with Ultralow Loss and Large Bandwidth - Yan Xiao; Yin Xu; Yue Dong; Bo Zhang; Yi Ni (Photonics, 2022)
Efficient fiber-to-chip coupling is a key issue in the field of integrated optics and photonics due to the lack of on-chip silicon light source at present. Here, we propose a silicon-based fiber-to-chip edge coupler by use of subwavelength grating (SWG)-assisted structure. The key conversion region is composed of a trident-shaped SWG in the center and two matched strip waveguides on both sides. To achieve high mode match between fiber mode and silicon waveguide mode and to realize low-loss transmission on-chip, we have divided the conversion region into three parts and determined their optimum dimensions. From results, the total device length is only 60 μm from input fiber to output silicon waveguide, and the insertion loss (IL) is as low as 0.23 dB at the wavelength of 1.55 μm. For the working bandwidth, its value can be enlarged to 240 nm (or 390 nm) by keeping IL < 1 dB (or 1.5 dB), which is quite promising for on-chip broadband devices. Based upon these advantages, we hope such a device could be applied in light coupling between optical fiber and on-chip silicon waveguide.